Relationship between vertical jump performance and playing time and efficiency in professional male basketball players - Cabarkapa, D.; Cabarkapa, D. V.; Aleksic, J.; Scott, A. A.; Fry, A. C. (Frontiers in Sports and Active Living, 2024)
With innovative force plate technology being available to many sports organizations worldwide that allow for time-efficient in-depth neuromuscular performance assessment, the purpose of the present study was to examine the relationship between some of the most commonly analyzed countermovement vertical jump (CVJ) force-time metrics and basketball playing time and efficiency. Twenty-four professional male basketball players volunteered to participate in the present study. The CVJ testing procedures were conducted within the first quarter of the competitive season span. Following a standardized warm-up protocol, each athlete stepped on a dual uni-axial force plate system sampling at 1,000 Hz and performed three maximum-effort CVJs with no arm swing. To minimize the possible influence of fatigue, each jump trial was separated by a 10-15 s rest interval and the average value across three jumps was used for performance analysis purposes. Basketball playing efficiency and average playing time were obtained at the end of the regular season competitive period from the coaching staff records and the official team records. Pearson product-moment correlation coefficients (r) were used to examine the strength of the relationships between force-time metrics and basketball playing time and efficiency, separately for each dependent variable (p < 0.05). A significant positive association was observed between playing efficiency and eccentric mean force and eccentric mean and peak power (r = 0.406-0.552). Similarly, an increase in eccentric mean power was positively correlated with the number of minutes played during the competitive season (r = 0.464). Moreover, the aforementioned relationship remained present even when eccentric mean power was expressed relative to the player's body mass (r = 0.406). Thus, the findings of the present study indicate that, at the professional level of men's basketball competition, CVJ eccentric strength and power have a positive impact on both playing time and efficiency.